A Systematic Review on Insights to Community Medicine and Clinical Research: Competency Training in Medical and Dental Education - Madeeha Minhas; Bilal Masood; Muhammad Hassaan Saeed; Amna Iqbal Butt; Fareed Ud Din Ahmad Chishti; Fatima Ali (Pakistan Journal of Medicine and Dentistry)
Background: Competency based training in medical and dental education has become important to train healthcare professionals to tackle clinical, cultural, and social aspects of healthcare. The innovations and developments in these training programs enabled a better understanding of healthcare and treatment planning. The purpose of this systematic review was to assess the implications of competency training in medical and dental curricula; more specifically, the incorporation of competency-based trainings with community medicine and research trials.